The fabrication and mechanical properties of a novel 3-component auxetic structure for composites. (29th September 2015) - Zhang, G.H.; Ghita, O.; Evans, K.E.
Abstract: Functional auxetic composite materials can be fabricated from conventional or from auxetic components. The helical auxetic yarn (HAY) is a recently invented auxetic reinforcing component for composite materials. This paper investigates the Poisson's ratio behaviour of a further development of the HAY, needed for many practical applications. The 3-component auxetic yarn is based on a stiff wrap fibre (the first component) helically wound around an elastomeric core fibre (the second component) coated by a sheath (the third component). The resultant structure can overcome problems such as slippage of the wrap and changes in wrapping angles previously encountered during the manufacture and utilisation of the two-component HAY. The mechanical performance of conventional and novel systems is investigated; with emphasis on the differences between the engineering and true Poisson's ratio. The importance of the utilisation of a true tensile modulus and a true Poisson's ratio is demonstrated. This is the first time reported in the literature that an experimental auxetic effect analysis of HAYs was carried out by comparing true and engineering Poisson's ratio. We show that depending on the coating thickness of the third component, the 3-component auxetic system can demonstrate auxetic behaviour, and the coating thickness can be employed as a new design parameter to tailor both the Poisson's ratio and modulus of this novel composite reinforcement for a wide range of applications.